Improvement in quality of life comparing noninvasive versus invasive hearing rehabilitation in children - Urík, Milan; Šikolová, Soňa; Hošnová, Dagmar; Kruntorád, Vít; Bartoš, Michal (Laryngoscope investigative otolaryngology, 2023)
Objectives The young population requires early rehabilitation of their hearing loss for normal cognitive, auditive hence social development. All of which, in turn, may have an impact on quality of life (QoL). This study aims to evaluate QoL between two different bone conduction (BC) hearing devices: a noninvasive adhesive hearing aid (Adhear [ADH]) vs. an active transcutaneous implant (Bonebridge [BB]). Methods This study composed of 12 BB and 15 ADH users. Pure tone as well as speech in noise and quiet measurements were evaluated and compared to the Assessment in QoL questionnaire (AQoL‐6d). Results Freefield results showed significant improvements for both devices compared to the unaided condition (p < .0001). Emphasis needs to be drawn on the different unaided level of conductive hearing loss as well as the indication range for both evaluated device groups: the ADH subjects exhibited a mean BC value of 9.50 ± 7.96 dB HL (the indication range up to 25 dB) and the BB subjects a mean of 23.33 ± 25.66 dB HL (the indication range up to 45 dB). Speech perception in quiet and in noise was significantly improved (p < .05; p < .001, respectively). QoL was significantly improved for both treatments (p < .05) but was not different among the devices, and the values were similar to their normal hearing, age, and sex‐matched control group. High correlations were found between QoL utility scores and improved PTA4 in the aided condition (r2 = .8839 and .7810 for BB and ADH, respectively). Conclusion Our results show that both devices offer significant beneficial audiological rehabilitations with significantly increased QoL. However, the underlying condition and the unaided degree of hearing loss, hence the required higher stimulation must be the deciding factor when opting for a hearing device, and this should be independent of age. Level of evidence 2c. This study aims to evaluate QoL in two different bone conduction (BC) hearing devices: a noninvasive adhesive hearing aid (Adhear [ADH]) versus an active transcutaneous implant (Bonebridge [BB]). QoL was significantly improved for both treatments (p < .05) but was not different among the devices and values were similar to their normal hearing, age‐ and sex‐matched control group. Our results show that both devices offer significant beneficial audiological rehabilitations with significantly increased QoL.